Public Awareness Of Conservation Area At Karimun Jawa - Taali, Muhammad; Supriyanto, Muhammad; Farani, Dinesh Basti; Puspitasari, Dyah Ayu Kunthi; Amri, Lala Hucadinota Ainul (Universitas AMIKOM Yogyakarta, 2023)
Tourism has become one of the major industries of many countries in the world. Do not miss the Indonesian state which is trying to take opportunities from the industry. In Indonesia, in the last five years, development has been very rapid because each region is trying to optimize its regional potential to boost the tourism industry. This is supported by the existence of regional autonomy which gives freedom to the regions to maximize the utilization of their potential to increase local revenue. The development of this potential is carried out by taking into account sustainable development along with the potentials and problems that each region has. A conservation area is an area or area that has been determined by the government as an area that must be protected so that the condition of the area remains sustainable. The importance of providing awareness and understanding (public awareness) about the conservation area is expected that the community will be able to play an active role in efforts to preserve the area. Based on this description, it is very important to make efforts to create public awareness in the Karimun Jawa Conservation Area. This activity is expected to increase awareness and understanding (public awareness) about conservation areas.